SCREENING AND IDENTIFICATION OF HEAVY METAL-TOLERANT ENDOPHYTIC FUNGI LASIODIPLODIA THEOBROMAE FROM BOSWELLIA OVALIFOLIOLATA AN ENDEMIC PLANT OF TIRUMALA HILLS - AISHWARYA, SANI; VENKATESWARULUNAGAM,; NETALA, VASUDEVA REDDY; TARTTE, VIJAYA (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Aim: The aim of this study was to evaluate the heavy metal resistance potentiality of endophytic fungi isolated from the leaves of Boswellia ovalifoliolata, an endemic medicinal plant of Tirumala Hills. Methods: Initially, isolation of fungal endophytes was carried out. Isolated fungi were screened for the heavy metal resistance against Co, Cd, Cu and Zn using growth and evaluated their maximum tolerant capacity. Molecular identification of endophytic fungi was carried out by 18S rRNA gene amplification and Sanger's nucleotide sequencing. Phylogenetic tree was constructed using NCBI Clustal W. Results: Ten different endophytic fungi were isolated from the leaves of B. ovalifoliolata. Among the isolated endophytic fungi, five showed resistance to Co, Cd, Cu, and Zn. The most resistant fungus was identified as Lasiodiplodia theobromae based on 18S rRNA gene sequencing. Conclusions: L. theobromae was isolated from B. ovalifoliolata and identified as one of the useful fungi involved in mycoremediation against heavy metal toxicity. Keywords: Heavy metals, Endophytic fungi, Endemic plant, Bioremediation.